Exploring English language teachers’ use of translanguaging in Indonesian secondary school English classrooms: reasons and purposes - Agustin, Dery Tria; Widagsa, Rudha; Yana, Pramugara Robby; Hamdani, Haris; Sagita, Yusti; Aini, Yasmin Qurrota; Hasanah, Nikmah Tul (Erudita: Journal of English Language Teaching, 2025)
Despite a growing body of research on translanguaging internationally, more studies are needed to examine secondary school teachers’ reasons and purposes of translanguaging during English lessons, especially in Outer Circle countries such as Chile, Germany, China, Vietnam, and Indonesia. This paper aims to contribute to this emerging area of interest by investigating junior secondary school teachers’ reasons for and purposes of utilizing students’ linguistic repertoires during English language instruction in the Indonesian ELT context. Data were primarily collected through interviews with three teachers working at two schools in the Special Region of Yogyakarta, Indonesia. The findings reveal several reasons for translanguaging, including limited exposure to English outside the classroom, lack of foundational English knowledge, restricted vocabulary, and diverse student learning needs and proficiency levels. Teachers reported using languages other than English to build rapport, foster a relaxed classroom atmosphere, reinforce or clarify instructions, facilitate comprehension, check understanding, and manage instructional time efficiently. These findings suggest that translanguaging can be an effective pedagogical strategy in English language classrooms, particularly in contexts with limited English exposure. The study points out the importance of incorporating translanguaging approaches into teacher education programs and recommends further research into its long-term effects on student learning outcomes.